2021
DOI: 10.1038/s41467-021-22235-8
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-occurring spinosyn A and its derivatives function as argininosuccinate synthase activator and tumor inhibitor

Abstract: Argininosuccinate synthase (ASS1) is a ubiquitous enzyme in mammals that catalyzes the formation of argininosuccinate from citrulline and aspartate. ASS1 genetic deficiency in patients leads to an autosomal recessive urea cycle disorder citrullinemia, while its somatic silence or down-regulation is very common in various human cancers. Here, we show that ASS1 functions as a tumor suppressor in breast cancer, and the pesticide spinosyn A (SPA) and its derivative LM-2I suppress breast tumor cell proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Then, tissues had been cultivated with 3,3‐Diaminobenzidine (DAB) for 1 minute and counterstained with hematoxylin. For hematoxylin and eosin (HE) staining [ 19 ], lung tissues were fixed in 10% buffered formalin and embedded in paraffin. Sections at 5 µm thickness were stained with hematoxylin and eosin solution followed by dehydration with graded alcohol and clearing in xylene.…”
Section: Methodsmentioning
confidence: 99%
“…Then, tissues had been cultivated with 3,3‐Diaminobenzidine (DAB) for 1 minute and counterstained with hematoxylin. For hematoxylin and eosin (HE) staining [ 19 ], lung tissues were fixed in 10% buffered formalin and embedded in paraffin. Sections at 5 µm thickness were stained with hematoxylin and eosin solution followed by dehydration with graded alcohol and clearing in xylene.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that spinosyn A and its derivative LM-2I exhibit anti-tumor function, which is regulated by activation of ASS1. Mechanistically, spinosyn A binds to ASS1 at the 97th cysteine site in tumor cells, thus increasing ASS1 enzymatic activity and anti-tumor effect (Zou et al, 2021). Currently, the investigation on the development of ASS1 activators is still limited, it is still required to explore deeper to identify the safety and efficacy of ASS1 activators.…”
Section: Development Of Ass1 Activator For Cancer Treatmentmentioning
confidence: 99%
“…ASS1 is known as the rate-limiting enzyme in arginine metabolism [28]. Notably, recent studies deepened our insights into the role of ASS1 as a novel tumor suppressive character [17,29]. Thus, we were urged to explore the biological association of PGAM1 and ASS1.…”
Section: Ass1 Is Identified To Be Upregulated In Pgam1 Knockdown Bc C...mentioning
confidence: 99%
“…Nevertheless, most treatment strategies for ASS1-deficient tumors neglect the tumor-suppressive effect of ASS1. Actually, the method of reconstructing the activity or expression of ASS1 in cancer cells is particularly important for tumor therapy [17]. In BC, Zou et al [17] discovered that spinosyn A and its derivatives significantly inhibit tumor growth by activation of ASS1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation